A case of buprenorphine-precipitated withdrawal managed with high-dose buprenorphine. (26th June 2021) - Quattlebaum, Thomas H N; Kiyokawa, Miki; Murata, Kayla A
Abstract: Background: Buprenorphine–naloxone has a very high affinity for the mu-receptor and can cause precipitated opioid withdrawal, typically more severe than withdrawal that occurs naturally, when administered while a full mu-opioid receptor agonist remains in a person's system. To avoid precipitated withdrawal, one needs to be in mild to moderate opioid withdrawal at the time of buprenorphine-naloxone induction. Recently, there have been reported cases of precipitated withdrawal occurring in patients taking fentanyl knowingly or unknowingly, despite them being in adequate opioid withdrawal at the time of induction. When this occurs, the current recommendation is to provide 2 mg of buprenorphine–naloxone every 1–2 hours. Objectives: Describe a case of successful management of buprenorphine-precipitated withdrawal with escalation of the dose of buprenorphine and highlight implications for future management. Methods: We present a case of a patient with a history of opioid use disorder who was in moderate opioid withdrawal at the time of buprenorphine–naloxone induction and experienced precipitated withdrawal after buprenorphine–naloxone administration. Results: High-dose buprenorphine–naloxone was given to the patient and precipitated withdrawal subsided after receiving a total of 20 mg. On the next day, the patient had no symptoms of opioid withdrawal and is currently maintained on 16 mg/day. Conclusion: With the rising prevalence of fentanyl-laced drugs, increased instances of precipitated withdrawal are likely to be encountered. In cases of precipitated withdrawal, giving a high dose of buprenorphine–naloxone rapidly is safe and will allow rapid reversal of withdrawal symptoms.